Edukasi Pengolahan Sampah Di SMA Negeri 6 Kabupaten Gorontalo Utara - Irawaty Hadi; Sry Endang Saleh; Ramla Hartini Melo (Universitas Negeri Gorontalo, 2026)
Waste management is one of the environmental problems that continues to increase along with population growth and community activities in North Gorontalo Regency. The low level of public awareness in implementing the 3R principles (Reduce, Reuse, Recycle) has caused waste generation to become increasingly difficult to control and has negatively affected the environment and public health. This waste management education program was conducted in February 2026 in Class 11 B of SMA Negeri 6 Gorut using socialization, discussion, and evaluation methods through observation of student participation during the activities. The materials presented included the definition of waste, types of waste, the environmental impacts of waste, the 3R concept, household waste sorting, compost production, and waste management through the Waste Bank program. The results of the activity showed that students were enthusiastic in participating in the educational sessions and actively engaged in discussions and question-and-answer activities. Students began to understand the importance of waste management and the implementation of simple habits such as sorting waste, reducing the use of single-use plastics, and maintaining the cleanliness of the school and home environment. This activity is expected to increase students’ awareness and concern regarding waste management as an effort to create a clean and healthy environment.